Managing radical innovation: The importance of specialized knowledge in the biotech revolution - Junkunc, Marc T. (Journal of Business Venturing, 2007)
This work has implications for managers, investors and entrepreneurs in times of breakthrough innovation at the firm or industry level. The work shows that the marketplace understands the importance of retaining and motivating critical specialized knowledge. By analyzing initial public offerings during the biotechnology discovery wave I find evidence that a dramatic decrease in the ability to include secondary shares (liquidity for early investors and entrepreneurs) in biotechnology IPOs corresponds with the radical increase in the importance of specialized knowledge in that industry, at the time of the rDNA breakthrough discovery and development.